The effectiveness of leadership styles among academic and research librarians in Eastern and Southern Africa: A comparative study. Issue 6 (13th August 2018) - Kwanya, Tom; Stilwell, Christine
Abstract : Purpose: The purpose of this paper is to investigate the leadership styles that academic and research librarians apply as well as their effectiveness in meeting their institutions' strategic objectives. The study also compared and contrasted the leadership styles and their corresponding impact in the effective delivery of academic and research library services in Kenya and South Africa. Design/methodology/approach: The study applied a survey research technique to garner the opinions of the librarians about the leadership styles of their leaders. Primary data were collected through key informant interviews with academic and research librarians. Additional data were collected through documentary analysis. The data were analysed and processed through content analysis. Findings: The findings indicate that most academic and research library leaders in South Africa and Kenya embrace a democratic leadership style. The results also show that most academic and research librarians hold the view that the leadership styles of their managers have a great impact on their individual performance and overall organisational effectiveness. Practical implications: The results of the study can be used to recommend or adopt leadership styles which have a higher potential of making a greater impact in Kenyan and South African academic and research libraries. The results can also be used as the basis for relevant curricula and policy development. Originality/value: The role of university librarians as leaders and the determinants of the effectiveness of academic and research library leaders, including leadership styles, have received minimal attention from scholars, particularly those in Africa. This study addresses the gap as it investigated the impact of the leadership styles of academic and research librarians on the effectiveness of their institutions, compared the academic and research library leadership scenarios in South Africa with Kenya, and makes recommendations on how to enhance leadership effectiveness.